Application of selected balancing methods for analysis and evaluation of the working efficiency of the assembly line on the example of a selected product - Antosz, Katarzyna; Kluz, Rafał (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2020)
Economic development requires from production companies to use more and more effective production methods. The growing demand for goods requires from them to reduce the lead time and to produce products of the best quality and competitive price. One of the problems of production lines is their proper balance. Balancing the production line consists in finding the optimal order of performed operations and assigning operations to individual operations in such a way, that work on positions is comparable. In this way, it is strive to minimize machine downtime and to distribute the work evenly between them. In the work, the performance analysis of the assembly line was made on the example of a selected product using three methods of balancing: the experimental method, the RPW (Ranked Positional Weight) heuristic method and SPT (Shortest Processing Time) method. The obtained results were analyzed and solutions were proposed to improve the work of the line. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)